Solving unit commitment using Shuffled Frog Leaping Algorithm (SFLA) / Fashirul Azmeer Mohd Fadzil - Mohd Fadzil, Fashirul Azmeer (2015)
This thesis presents a solution to Unit Commitment (UC) problem of generating units based on Shuffled Frog Leaping Algorithm (SFLA). The proposed SFLA in this study is developed using Matlab programming. This method is applied to the IEEE 30 bus with 6 units system for one day scheduling period. The simulation results obtained using the proposed algorithm show that the minimum cost can be obtained for the schedule.